2017
DOI: 10.1111/1756-185x.13240
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis and periodontal disease: What are the similarities and differences?

Abstract: Rheumatoid arthritis (RA) and periodontal disease (PD) are chronic inflammatory diseases that share similar osteoclasia, human leukocyte antigen-DR4 allelic genes and immunological profile, and characteristic cytokines. Smoking can contribute to more severe RA and PD; secretion of pro-inflammatory mediators destroys the soft synovial membrane and periodontium, respectively. Anti-citrullinated protein antibodies and anti-α-enolase antibody are characteristic of these two diseases. Some studies suggest that PD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 103 publications
3
25
1
1
Order By: Relevance
“…These findings were similar to those in previous studies 19,25 where it was shown that RA was common in females and older-aged participants. Interestingly, non-smokers had a higher prevalence of RA in our study although the findings from some previous studies contradict ours, 22,26 while findings from other studies corroborate ours. 27 In addition, the non-drinkers in our study had a higher prevalence of RA, different from the outcome of the previous study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These findings were similar to those in previous studies 19,25 where it was shown that RA was common in females and older-aged participants. Interestingly, non-smokers had a higher prevalence of RA in our study although the findings from some previous studies contradict ours, 22,26 while findings from other studies corroborate ours. 27 In addition, the non-drinkers in our study had a higher prevalence of RA, different from the outcome of the previous study.…”
Section: Discussionsupporting
confidence: 56%
“…RA and periodontitis are chronic inflammatory diseases that share similar etiologies: human leukocyte antigen-DR4 allelic genes, a specific immunological profile, and characteristic cytokines. 22 Cross-sectional analysis performed in this study indicated that the prevalence of periodontitis in RA patients (19.6%) was higher than in the participants without RA (16.6%) ( Table 1), and the prevalence of RA in periodontitis patients (6.2%) was higher than in the individuals without periodontitis (5.2%) ( Table 2). These findings are in agreement with our previous study 19 where the prevalence of periodontitis in RA patients (28.4%) was higher than that in participants without RA (27.9%).…”
Section: Discussionmentioning
confidence: 60%
“…Some studies discuss the relationship between the periodontal disease and rheumatoid disease. Both diseases have the same risk factors, such as genetic predisposition, abnormal host inflammatory response, infection and inflammation, and smoking, and are characterized by increased secretion of pro‐inflammatory mediators . Additionally, there is the question of whether PD can be a feature of RA .…”
Section: Discussionmentioning
confidence: 99%
“…Current findings strongly support the hypothesis that chronic periodontal disease could be related to the initiation and maintenance of the autoimmune inflammatory responses that occur in RA. It was also stated that periodontal treatment decreased disease activity score, including Disease Activity Score of 28 joints—C‐reactive protein (DAS28‐CRP), immunoglobulin G (IgG) serum level to Porphyromonas gingivalis and citrulline …”
Section: Introductionmentioning
confidence: 97%
“…The relation between oral health and general health is currently widely described and documented [ 1 , 2 ]. In several studies, oral infection with periodontal disease (PD) has been associated with systemic conditions, such as diabetes, cardiovascular disease, pulmonary infection, liver diseases, strokes, ankylosing spondylitis, and rheumatoid arthritis (RA) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%